2021
DOI: 10.1108/jm2-08-2020-0207
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of enablers of cloud technology to boost industry 4.0 adoption in the manufacturing micro, small and medium enterprises

Abstract: Purpose Cloud technology is extremely critical for the continuing progress of Industry 4.0 and it helps in pooling centralized information for the business. Further, it offers a platform for collaboration for improving the performance of the industry. This paper aims to investigate the factors affecting the implementation of cloud technology for boosting Industry 4.0 adoption in micro, small and medium enterprises (MSMEs) of the manufacturing sector. Design/methodology/approach A total of 14 enablers were co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(7 citation statements)
references
References 58 publications
0
6
1
Order By: Relevance
“…The ability of technology to track competitors' success was not a major concern for most respondents in this study. This is contrary to previous studies, such as that of reference [120][121][122][123][124], that found a significant relationship between observability and technology implementation. This research is in line with the study conducted by reference [97,129].…”
Section: Resultscontrasting
confidence: 99%
See 1 more Smart Citation
“…The ability of technology to track competitors' success was not a major concern for most respondents in this study. This is contrary to previous studies, such as that of reference [120][121][122][123][124], that found a significant relationship between observability and technology implementation. This research is in line with the study conducted by reference [97,129].…”
Section: Resultscontrasting
confidence: 99%
“…The literature clearly shows that the chance to trial a technology greatly improves its likelihood of implementation. Implementation of cloud technology was studied by reference [121] and found trialability to be a major factor that affected its implementation in micro, small and medium enterprises. A study by reference [91] similarly found a clear connection between trialability and technology implementation.…”
Section: Hypothesis Development Of Trialabilitymentioning
confidence: 99%
“…, 2018), which were conducted in the manufacturing industry of western countries such as Denmark, Norway and Germany, respectively. Similarly, in the eastern context, Jain and Ajmera (2020) and Subramanian et al. (2021) did not report these factors.…”
Section: Discussionmentioning
confidence: 85%
“…In total interpretive structural modelling (TISM) the levels of relationships are not considered, but only binary values, that is, 1: if the relationship exists between the variables; and 0: for no relationship (Gardas et al, 2021; Subramanian et al, 2021). This approach does not offer rankings of the variables, whereas, DEMATEL can rank them.…”
Section: Methodology and Cause‐effect Model Developmentmentioning
confidence: 99%